A Review of Treatment of Coronavirus Disease 2019 (COVID-19): Therapeutic Repurposing and Unmet Clinical Needs - Chen, Po-Lin; Lee, Nan-Yao; Cia, Cong-Tat; Ko, Wen-Chien; Hsueh, Po-Ren (Frontiers in Pharmacology, 2020)
For the initial phase of pandemic of coronavirus disease 2019 (COVID-19), repurposing drugs that in vitro inhibit severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have been attempted with overlooked or overestimated efficacy owing to limited clinical evidence. Most early clinical trials have the defects of study design, small sample size, non-randomized design, or different timings of treatment initiation. However, well-designed studies on asymptomatic or mild, or pediatric cases of COVID-19 are scarce and desperately needed to meet the clinical need. However, a trend could be observed based on current clinical evidence. Remdesivir and favipiravir may shorten the recovery time; lopinavir/ritonavir does not demonstrate treatment efficacy in severe patients. Triple therapy of ribavirin, lopinavir, and interferon β-1b showed early viral negative conversion, and the major effect may be related to interferon. Some small sample-size studies showed that interleukin-6 inhibitors may demonstrate clinical improvement; non-critical patients may benefit from convalescent plasma infusion in small sample-size studies; and the role of hydroxychloroquine or chloroquine in the treatment and prophylaxis of COVID-19 remains unclear. Combination therapy of traditional Chinese medicine with antiviral agents (ex. interferon, lopinavir, or arbidol) may alleviate inflammation in severe COVID-19 patients based on small sample-sized observational studies and experts’ opinion. Most of the published studies included severe or critical patients with COVID-19. Combination therapy of antiviral agents and immune-modulating drugs is reasonable especially for those critical COVID-19 patients with cytokine release syndrome. Drugs to blunt cytokine release might not benefit for patients in the early stage with mild disease or the late stage with critical illness. Traditional Chinese medicine with antiviral effects on SARS-CoV-2 and immune-modulation is widely used for COVID-19 patients in China, and is worthy of further studies. In this review, we aim to highlight the available therapeutic options for COVID-19 based on current clinical evidence and encourage clinical trials specific for children and for patients with mild disease or at the early stage of COVID-19.